Helmintos de tropidurus (Lacertilia, Iguanidae) da coleção helmintológica do Instituto Oswaldo Cruz - Vicente, Joaquim Júlio (1977)
After studying 245 samples of helminths recovered from Tropidurus torquatus (Wied) and Tropidurus spinulosus (Cope) all of them included in the Oswaldo Cruz Helmintological, Collection, we were able to present the attained results as follows: Plagiorchis freitasi n. sp. is proposed, as the first species under Plagiorchis Luehe, 1899, occurring in a reptilian host in Brazil, which is also applied to Oswaldocruzia mazzai Travassos, 1935. Strongyluris travassosi Alho, 1969 and Strongyluris freitasi Alho, 1969 are identified to Strongyluris oscari Travasses., 1923. Piratuba digiticauda Lent & Freitas, 1941, Salobrella interrnedia Freitas, 1941 and Physaloptera retusa are refered for the first time in Tropidurus torquatus (Wied) as well as Physaloptera lutzi Guimarães, Cristofaro e Rodrigues, 1976, Strongyluris oscari Travasses, 1923 and Parapharyngodo sceleratus (Travassos, 1923) in Tropidurus spinulosus (Cope). The nernatodes proved to be the most infecting group and the higher infection frequency being due to Paradistomum parvissimum Travasos, 1918 in Tropidurus torquatus (Wied) and Paraphyryngodon sceleratus (Travassos, 1923) in Tropidurus spinulosus (Cope). The digestive tract was found to be highly contaminated; the storn ach more frequently and the large iptestine presenting the higher infection rate. The same nematode species could be ascertained in both hosts. Trematodes, cestodes, acanthocephalans and linguatulids were not found among the samples recovered from Topidurus soinulosus (Cope), included in The Instituto Oswaldo Cruz Helminthological Collection, what can be associated to the few necropsies accomplished in this host.